The Role of the Monocyte–Macrophage System in the Pathogenesis of Acute Pancreatitis: A Review (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Acute pancreatitis (AP) is an inflammatory disease of the pancreas characterized by premature activation of digestive enzymes and acinar cell damage, leading to local and systemic inflammation. Recent studies have highlighted the crucial role of the monocyte–macrophage system in the pathogenesis of AP.